Development of Berberine-Loaded Nanoparticles for Astrocytoma Cells Administration and Photodynamic Therapy Stimulation - Sergio Comincini; Federico Manai; Milena Sorrenti; Sara Perteghella; Camilla D’Amato; Dalila Miele; Laura Catenacci; Maria Cristina Bonferoni (Pharmaceutics, 2023)
Berberine (BBR) is known for its antitumor activity and photosensitizer properties in anti-cancer photodynamic therapy (PDT), and it has previously been favorably assayed against glioblastoma multiforme (GBM)-derived cells. In this work, two BBR hydrophobic salts, dodecyl sulfate (S) and laurate (L), have been encapsulated in PLGA-based nanoparticles (NPs), chitosan-coated by the addition of chitosan oleate in the preparation. NPs were also further functionalized with folic acid. All the BBR-loaded NPs were efficiently internalized into T98G GBM established cells, and internalization increased in the presence of folic acid. However, the highest mitochondrial co-localization percentages were obtained with BBR-S NPs without folic acid content. In the T98G cells, BBR-S NPs appeared to be the most efficient in inducing cytotoxicity events and were therefore selected to assess the effect of photodynamic stimulation (PDT). As a result, PDT potentiated the viability reduction for the BBR-S NPs at all the studied concentrations, and a roughly 50% reduction of viability was obtained. No significant cytotoxic effect on normal rat primary astrocytes was observed. In GBM cells, a significant increase in early and late apoptotic events was scored by BBR NPs, with a further increase following the PDT scheme. Furthermore, a significantly increased depolarization of mitochondria was highlighted following BBR-S NPs’ internalization and mostly after PDT stimulation, compared to untreated and PDT-only treated cells. In conclusion, these results highlighted the efficacy of the BBR-NPs-based strategy coupled with photoactivation approaches to induce favorable cytotoxic effects in GBM cells.